Prenatal and Intrapartum Factors Associated With Infant Temperament: A Systematic Review - Takegata, Mizuki (Front Psychiatry, 2021)
Background: Temperament involves individual variations in behavioural tendencies of emotional responses and reactions to stimuli after birth. Because ‘foetal programming' is a strong hypothesis in developing temperament, prenatal and intrapartum factors may be significant determinants of infant temperament. This systematic literature review aims to elucidate the evidence of prenatal and intrapartum predictors, including genetic, biological, environmental, socio-demographic, psychological, and obstetric factors of parents and their child. Methods: Relevant articles were searched using MEDLINE, PubMed, and SCOPUS. The inclusion criteria were (a) original research article, (b) written in English, (c) assessed the temperament of infants 12 months old or younger as an outcome variable, and (d) investigated prenatal and intrapartum factorial variables of infant temperament. Following the PRISMA guideline, the articles found in the three databases were screened and selected according to the inclusion and exclusion criteria before the final review. Results: Finally, 35 articles were reviewed. This systematic review identified a variety of prenatal and intrapartum factors that were significantly associated with infant temperament: (1) genetic and biological factors: certain genotypes, maternal cortisol and ACTH, and CRHs, (2) environmental factors: substance use such as tobacco, alcohol, and illegal drugs, (3) socio-demographic factor: lower-income, (4) psychological factors: depression or anxiety, eating disorders, personality types of mothers, and domestic violence, and (5) obstetric factors: foetal growth (birth weight), hypertension in mothers, nausea (emesis), and preterm birth. Conclusion: The findings support gene-environment interaction and biological mechanisms for developing infant temperament, suggesting the importance of ensuring a safe and comfortable environment for pregnant mothers, unborn infants, and families during pregnancy and delivery.